De novo Sequencing and Transcriptome Analysis of Pinellia ternata Identify the Candidate Genes Involved in the Biosynthesis of Benzoic Acid and Ephedrine - Zhang, Guang-hui; Jiang, Ni-hao; Song, Wan-ling; Ma, Chun-hua; Yang, Sheng-chao; Chen, Jun-wen (Frontiers in Plant Science, 2016)
Background: The medicinal herb, Pinellia ternate, is purported to be an anti-emetic with analgesic and sedative effects. Alkaloids are the main biologically active compounds in P. ternata, especially ephedrine that is a phenylpropylamino alkaloid specifically produced by Ephedra and Catha edulis. However, how ephedrine is synthesized in plants is uncertain. Only the phenylalanine ammonia lyase (PAL) and relevant genes in this pathway have been characterized. Genomic information of P. ternata is also unavailable. Results: We analyzed the transcriptome of the tuber of P. ternata with the Illumina HiSeqTM 2000 sequencing platform. 66,813,052 high-quality reads were generated, and these reads were assembled de novo into 89,068 unigenes. Most known genes involved in benzoic acid biosynthesis were identified in the unigene dataset of P. ternate, and the expression patterns of some ephedrine biosynthesis-related genes were analyzed by reverse transcription quantitative real-time PCR (RT-qPCR). Also, 14,468 simple sequence repeats (SSRs) were identified from 12,000 unigenes. Twenty primer pairs for SSRs were randomly selected for the validation of their amplification effect. Conclusion: RNA-seq data was firstly used to provide a comprehensive gene information on P. ternata at the transcriptional level. These data will advance molecular genetics in this valuable medicinal plant.